2012
DOI: 10.1093/arclin/acr109
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Suboptimal Effort with Symbol Span: Development of a New Embedded Index

Abstract: Developing embedded indicators of suboptimal effort on objective neurocognitive testing is essential for detecting increasingly sophisticated forms of symptom feigning. The current study explored whether Symbol Span, a novel Wechsler Memory Scale-fourth edition measure of supraspan visual attention, could be used to discriminate adequate effort from suboptimal effort. Archival data were collected from 136 veterans classified into Poor Effort (n = 42) and Good Effort (n = 94) groups based on symptom validity te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
4
3
Order By: Relevance
“…This design differs from our study that recruited mixed-etiology neurological patients. Another study (Young et al, 2012) found that the SSP subtest differentiated well between adequate and inadequate effort in a mixed clinical group of veterans, which we did not find. However, no other WMS-IV subtests were administered in Young et al (2012).…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…This design differs from our study that recruited mixed-etiology neurological patients. Another study (Young et al, 2012) found that the SSP subtest differentiated well between adequate and inadequate effort in a mixed clinical group of veterans, which we did not find. However, no other WMS-IV subtests were administered in Young et al (2012).…”
Section: Discussioncontrasting
confidence: 98%
“…Another study (Young et al, 2012) found that the SSP subtest differentiated well between adequate and inadequate effort in a mixed clinical group of veterans, which we did not find. However, no other WMS-IV subtests were administered in Young et al (2012). Finally, it should be stressed that the authorized Dutch version of the WMS-IV is equivalent to the originally published U.S. version (Hendriks et al, 2014;Wechsler, 2009), with a similar factor structure (Bouman et al, 2015).…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations